2017
DOI: 10.1002/cyto.a.23079
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of dense cell cultures by multiwavelength lens‐free video microscopy

Abstract: They present results for lens-free microscopy for the imaging of dense cell culture. With this aim, they use a multiwavelength LED illumination with well separated wavelengths, together with the implementation of an appropriate holographic reconstruction algorithm. This allows for a fast and efficient reconstruction of the phase image of densely packed cells (up to 700 cells/mm ) over a large field of view of 29.4 mm . Combined with the compactness of the system which fits altogether inside an incubator, lens-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 35 publications
0
35
0
1
Order By: Relevance
“…It has taken the community many decades and great endeavor to segment, identify, and analyze cells for explaining the cellular and molecular processes of health and disease. Studies have showed that cell segmentation can contribute to the better cell recognition in various fields of cell biology (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and great advances have been achieved. However, it still has a long way to go before meeting the ultimate goal that the developed method can segment and identify different types of cells autonomously and the biologists can trust the segmentation and identification results blindly.…”
Section: The Future Of Cell Segmentationmentioning
confidence: 99%
“…It has taken the community many decades and great endeavor to segment, identify, and analyze cells for explaining the cellular and molecular processes of health and disease. Studies have showed that cell segmentation can contribute to the better cell recognition in various fields of cell biology (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and great advances have been achieved. However, it still has a long way to go before meeting the ultimate goal that the developed method can segment and identify different types of cells autonomously and the biologists can trust the segmentation and identification results blindly.…”
Section: The Future Of Cell Segmentationmentioning
confidence: 99%
“…Lens-free acquisitions were performed with a Cytonote microscope (Iprasense, Montpellier, France). This setup is inspired by the lens-free imaging system described in [17], which was modified to perform continuous monitoring of cellular cultures inside an incubator at a controlled temperature and humidity [15,16]. Multiple wavelength illumination is provided by a RGB LEDs with red (647 nm, FWHM 13 nm), green (527 nm, FWHM 21 nm) and blue (450 nm, FWHM 15 nm) color.…”
Section: Optical Setupmentioning
confidence: 99%
“…D in Eq. (15) measures the misfit between forward model predictions and actual measurements; since the variance of M Z is constant, equal to 1/4, the data matching term can be written as a χ 2 criterion: (16) where N p is the number of pixel of acquisition, N c is the number of color (here N c = 3) used and where for the sake of simplicity of the text, the symbol ∫ dì r is used to replace the discrete summation: for any function f , such an integral replace:…”
Section: A13 Optimization Criterionmentioning
confidence: 99%
See 1 more Smart Citation
“…To follow epithelium formation within the alginate tubes at large as well as cellular scales, we took advantage of a lens-free microscope that allows the acquisition of large fields of view (up to 29.4 mm 2 , CMOS sensor) over long period of time (days) directly into the incubator (Allier et al, 2017). After an holographic reconstruction process, it is possible to obtain a phase image of the biological sample.…”
Section: Three Main Stages Characterize Epithelia Growth In Alginate mentioning
confidence: 99%